2002
DOI: 10.1103/physrevstab.5.121002
|View full text |Cite
|
Sign up to set email alerts
|

Electron cloud simulations: beam instabilities and wakefields

Abstract: HEADTAIL is a simulation program developed at CERN which is aimed at studying the single-bunch instability arising from the interaction on successive turns of a single bunch with the cloud generated by the previous bunches. The code includes chromaticity, space charge tune spread, broad-band impedance, and detuning with amplitude for more realistic simulation. Examples of application are shown. Transverse and longitudinal wake functions are also outputs of the HEADTAIL code.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 7 publications
5
48
0
Order By: Relevance
“…Simulations performed with the HEADTAIL code [12] reproduce very well the observed travelling-wave pattern when a broad band impedance with characteristics (shunt impedance Z t , resonant frequency f res and quality factor Q) derived from beam-based measurements [13][14] is considered. The same simulations have shown that the threshold of the instability is consistent with the measured one for the same beam characteristics [6].…”
Section: Present Understanding Of the Instabilitymentioning
confidence: 99%
“…Simulations performed with the HEADTAIL code [12] reproduce very well the observed travelling-wave pattern when a broad band impedance with characteristics (shunt impedance Z t , resonant frequency f res and quality factor Q) derived from beam-based measurements [13][14] is considered. The same simulations have shown that the threshold of the instability is consistent with the measured one for the same beam characteristics [6].…”
Section: Present Understanding Of the Instabilitymentioning
confidence: 99%
“…The results have been benchmarked with three different simulation codes, namely HEAD-TAIL [7], QUICKPIC [9] and PEHTS [10]. The interaction between the electrons and the beam particles is expressed by the equation of motion dp p ds = − 2r e γ ∂φ e (r) ∂r dp…”
Section: Head-tail and Single-bunch Instabilitymentioning
confidence: 99%
“…Extensive studies on the possible electron cloud effect have been performed at SLAC for the GLC/NLC and the TESLA positron main DR [3,4,5] and the positron low emittance transport lines. The results are obtained by computer simulation codes HEAD-TAIL, QUICKPIC, PEHTS (single-bunch), CLOUD MAD (incoherent effects) and POSINST (coupled-bunch) [6,7,8,9,10] developed to study the electron cloud effect in particle accelerators. If the cloud is not suppressed, it will grow until it reaches an equilibrium density close to the neutralization level, ratio e/p=1, but in most cases the beam-cloud interaction sets a much lower limit on the acceptable cloud density.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the transverse beam sizes are scaled as 1= p . The dependence of the ECI threshold on energy was simulated with the HEADTAIL code [8]. The action of the electron cloud on the bunch is lumped in one or more points along the ring.…”
mentioning
confidence: 99%